Comparative study of incidence, risk factors, etiological agents and outcome of early and late ventilator associated pneumonia in paediatric intensive care unit at a tertiary care centre - Malhotra, Preeti; Kumar, Naresh; Thapar, Karuna; Bagga, Amanjeet Kaur (International Journal of Contemporary Pediatrics, 2018)
Background: Ventilator Associated Pneumonia (VAP), the nosocomial pneumonia developing in mechanically ventilated patients after 48 hours of mechanical ventilation, is the second most common nosocomial infection in the paediatric intensive care unit (PICU). VAP occurring within 96 hours of initiation of mechanical ventilation is termed as early VAP and later than that is known as late VAP. The aim of this study was to determine the incidence rate, risk factors and bacteriological profile and outcome of early and late ventilator associated pneumonia in PICU. Methods: The study was conducted from December 2015 to November 2017 in which 89 children beyond 1 year of age were ventilated for more than 48 hours of which those who developed VAP as per CDC criteria were enrolled in the study. The endotracheal secretions were collected, processed and recorded as per standard microbiological methods. Statistical associations were further evaluated between various parameters of VAP and time of development of VAP. Results: Of all the mechanically ventilated patients, 33.7% developed VAP. Incidence of Early VAP was 23.3% and that of Late VAP was 76.67%. Duration of mechanical ventilation and re-intubation were significantly associated with the time of development of VAP. Micro-organisms identified by culture, involved in the aetiology of VAP were: gram-negative bacteria in 74.9% and gram-positive bacteria in 25.1%. The overall mortality rate was 43.33%. Conclusions: Re-intubation and duration of mechanical ventilation are a significant risk factor for development of late VAP. Overall the most common Gram-negative bacteria associated with VAP was Acinetobacter baumanii. The most common isolate in early VAP was Acinetobacter baumanii whereas infections by Pseudomonas and E. coli are common in late VAP. population.